International mechanisms for threat reduction of chemical and biological weapons. - Smithson, A.E.
Discusses steps the United States needs to take to strengthen current global initiatives. If U.S. policymakers want the Chemical Weapons Convention (CWC) and the Biological and Toxin Weapons Convention (BWC) to be effective threat-reduction mechanisms, they must replace rhetoric with action. In this age, the United States government can ill afford to neglect any mechanism that has a constructive role to play in lowering the threat that nations or terrorists might obtain and unleash chemical and biological weapons. This article outlines several steps that the United States can take in the near term to put the BWC and the CWC on stronger footing. Otherwise, the United States will have to shoulder the lion's share of the blame for the weakened status of these treaties.
Keywords: Biological & Toxin Weapons Convention; Chemical Weapons Convention; U.S. policymakers; United States government; Biological weapons; Chemical weapons; Current global initiatives strengthening; International mechanisms; Nations; Rhetoric with action; Terrorists; Threat reduction